SELECTION OF ALTERNATIVE LOCATIONS FOR MUNICIPAL WASTE LANDFILLS USING GIS AND REMOTE SENSING TECHNOLOGIES - Karimov Farokhiddin; Tobirov Odiljon (TADQIQOTLAR, 2025)
Abstract: Rapid urbanization and population growth have significantly intensified municipal solid waste management challenges, making the selection of suitable landfill sites a critical issue for environmental sustainability and public health. This article examines the application of Geographic Information Systems (GIS) and remote sensing technologies for identifying alternative locations for municipal waste landfills. The study synthesizes existing methodologies and case studies to evaluate environmental, socioeconomic, and infrastructural criteria influencing landfill site suitability. Multi-criteria decision-making techniques, including the Analytical Hierarchy Process (AHP) and weighted spatial analysis, are emphasized as effective tools for integrating diverse datasets such as land use, topography, proximity to water resources, transportation networks, and population density. The findings highlight that the integration of GIS and remote sensing enhances the accuracy, transparency, and efficiency of landfill site selection, while minimizing potential environmental risks and social conflicts. The article concludes that geospatial-based approaches provide a robust scientific framework for sustainable municipal waste management and support informed decision-making aligned with long-term urban development and environmental protection goals.